Deciphering the Emulsification Process to Create an Albumin-Perfluorocarbon-(o/w) Nanoemulsion with High Shelf Life and Bioresistivity - Jaegers, Johannes (Langmuir : the ACS journal of surfaces and colloids, 2022)
This work aimed at the development of a stable albumin-perfluorocarbon (o/w) emulsion as an artificial oxygen carrier suitable for clinical application. So far, albumin-perfluorocarbon-(o/w) emulsions have been successfully applied in preclinical trials. Cross-linking a variety of different physical and chemical methods for the characterization of an albumin-perfluorocarbon (PFC)-(o/w) emulsion was necessary to gain a deep understanding of its specific emulsification processes during high-pressure homogenization. High-pressure homogenization is simple but incorporates complex physical reactions, with many factors influencing the formation of PFC droplets and their coating. This work describes and interprets the impact of albumin concentration, homogenization pressure, and repeated microfluidizer passages on PFC-droplet formation; its influence on storage stability; and the overcoming of obstacles in preparing stable nanoemulsions. The applied methods comprise dynamic light scattering, static light scattering, cryo- and non-cryo-scanning and transmission electron microscopies, nuclear magnetic resonance spectroscopy, light microscopy, amperometric oxygen measurements, and biochemical methods. The use of this wide range of methods provided a sufficiently comprehensive picture of this polydisperse emulsion. Optimization of PFC-droplet formation by means of temperature and pressure gradients results in an emulsion with improved storage stability (tested up to 5 months) that possibly qualifies for clinical applications. Adaptations in the manufacturing process strikingly changed the physical properties of the emulsion but did not affect its oxygen capacity